2005
DOI: 10.1093/cercor/bhi062
|View full text |Cite
|
Sign up to set email alerts
|

White Matter Development During Childhood and Adolescence: A Cross-sectional Diffusion Tensor Imaging Study

Abstract: Maturation of brain white matter pathways is an important factor in cognitive, behavioral, emotional and motor development during childhood and adolescence. In this study, we investigate white matter maturation as reflected by changes in anisotropy and white matter density with age. Thirty-four children and adolescents aged 6-19 years received diffusion-weighted magnetic resonance imaging scans. Among these, 30 children and adolescents also received high-resolution T1-weighed anatomical scans. A linear regress… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

60
568
1
4

Year Published

2007
2007
2017
2017

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 757 publications
(633 citation statements)
references
References 67 publications
60
568
1
4
Order By: Relevance
“…One study reported an association between impairments in global shape perception in the GL and MPP tasks and in face discrimination abilities in adults with autism [Behrmann et al, 2006]. Our finding that adolescence is a particularly vulnerable developmental period in autism for global shape perception is important in light of the findings that this is a critical time for the functional and structural development of the ventral visual stream, which is implicated in object form, shape, and identity coding [Bachevalier, Hagger, & Mishkin, 1991;Barnea-Goraly et al, 2005;Gogtay et al, 2004;Scherf, Behrmann, Humphreys, & Luna, 2007] and appears to be abnormal in children and adolescents [Grelotti, Gauthier, & Schultz, 2002;Wang, Dapretto, Hariri, Sigman, & Bookheimer, 2004] and adults with ASD [Ashwin, Baron-Cohen, Wheelwright, O'Riordan, & Bullmore, 2007;Bailey, Braeutigam, Jousmaki, & Swithenby, 2005;Humphreys, Hasson, Avidan, Minshew, & Behrmann, 2008;Pierce, Muller, Ambrose, Allen, & Courchesne, 2001;Schultz et al, 2003]. These neural differences may be present throughout development in HFA individuals and might serve as the basis for the atypical maturation of perceptual organization and the failure to develop mature global shape processing in adolescence.…”
Section: Discussionmentioning
confidence: 92%
“…One study reported an association between impairments in global shape perception in the GL and MPP tasks and in face discrimination abilities in adults with autism [Behrmann et al, 2006]. Our finding that adolescence is a particularly vulnerable developmental period in autism for global shape perception is important in light of the findings that this is a critical time for the functional and structural development of the ventral visual stream, which is implicated in object form, shape, and identity coding [Bachevalier, Hagger, & Mishkin, 1991;Barnea-Goraly et al, 2005;Gogtay et al, 2004;Scherf, Behrmann, Humphreys, & Luna, 2007] and appears to be abnormal in children and adolescents [Grelotti, Gauthier, & Schultz, 2002;Wang, Dapretto, Hariri, Sigman, & Bookheimer, 2004] and adults with ASD [Ashwin, Baron-Cohen, Wheelwright, O'Riordan, & Bullmore, 2007;Bailey, Braeutigam, Jousmaki, & Swithenby, 2005;Humphreys, Hasson, Avidan, Minshew, & Behrmann, 2008;Pierce, Muller, Ambrose, Allen, & Courchesne, 2001;Schultz et al, 2003]. These neural differences may be present throughout development in HFA individuals and might serve as the basis for the atypical maturation of perceptual organization and the failure to develop mature global shape processing in adolescence.…”
Section: Discussionmentioning
confidence: 92%
“…Of particular interest was the anatomy of white matter. White matter changes are thought to be a key process in postnatal brain development, which continues throughout childhood and adolescence into early adulthood (Barnea‐Goraly, 2005; Muftuler et al., 2012; Qiu, Tan, Zhou, & Khong, 2008; Tau & Peterson, 2010). In particular, the myelination of axons is thought to be a critical mechanism of brain development in this age range (Miller et al., 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Such large-scale genomic data combined with the high density of information provided by a contectome database will be transformative. By combining the information in these databases we can now begin to explore the genomic determinants of neuronal network topology, network myelination (by combining our techniques with diffusivity, magnetization transfer or T1 relaxation measurements (Barnea-Goraly et al, 2005;Gogtay et al, 2004;Xydis et al, 2006)), network information flow and functional interaction (using EEG and MEG).…”
Section: Neuro-science Questions That May Benefit From Connectomicsmentioning
confidence: 99%